Nonclassical symmetry analysis and heir-equations of forced Burger equation with time variable coefficients - Gulsen, Selahattin; Hashemi, M. S.; Alhefthi, Reem; İnç, Mustafa; Bicer, Harun (Springer Heidelberg, 2023)
The current paper raises notice of a novel approach known as the heir-equations method. Nucci, for the first time in the literature, discovered that iterating the nonclassical symmetry method to generate new nonlinear equations secures the Lie point symmetry properties of the given equation, or, in other words, inherits them. The technique that corresponds to non-classical symmetries is particularly powerful in obtaining new solutions to evolutionary-type equations. In this article, new solutions and nonclassic symmetries of the coefficient-variable forced Burger equation are obtained by the heir-equations method.
Keywords: Nonclassical symmetry; Heir-equation method; Forced Burger equation